Analysis on the relation between velocity and power values during propulsive phase of bench throw exercise and upper-body strength characteristics in professional handball players - Can, I. (European Journal of Physical Education and Sport Science, 2018)
The purpose of this study is to analyze the relation between velocity and power values during propulsive phase of bench throw exercise and upper-body strength characteristics in professional handball players and to determine whether upper-body strength characteristics have a significant effect on velocity and power parameters. In accordance with this purpose, a total of 13 professional handball players competing in Turkish Handball 1. League (age: 25.4 ± 3.86 years; height: 187.5 ± 8.33 cm; body weight: 90.9 ± 14.8 kg) voluntarily participated in the research. In this study, maximal dynamic strength test was applied in bench press (BP) exercises in addition to the right and left hand grip strength test with the purpose of determining the upper-body strength characteristics. In order to determine velocity and power parameters, bench throw (BT) exercises were applied by using an external load that corresponds to 30% of body weights of the participants via an isoinertial velocity converter (T-Force dynamic measurement system) and values of mean propulsive velocity (MPV), peak velocity (PV), mean propulsive power (MPP) and peak power (PP) were obtained. Descriptive statistics, Spearman correlation analysis and Kolmogorov-Smirnov normality tests were used in order to analyze data. According to analysis results, while mean one-repetition maximal (1RM) strength values of the participants in BP exercise were obtained as 97.8 (± 15.0 kg), their right and left hand grip strength values were respectively obtained according to the order specified as 55.4 (± 8.16 kg) and 53.7 (± 5.81 kg). It has been concluded that while there is a statistically positive and significant relation between the MPV (r = .674, p < 0.05; r = .698, p < 0.01, respectively) and PV values (r = .644; r = .670, p < 0.05, respectively) of the participants in BT exercises and both right and left hand grip strength values, there isn`t any statistical relation in terms of the MPP (r = .528; r = .456, p > 0.05, respectively) and PP values (r = .487; r = .401, p> 0.05, respectively). It has also been concluded that there is a statistically positive and highly significant relation between 1RM strength values in BP exercises of the participants and MPV (r = .728), PV (r = .775), MPP (r = .703) and PP (r = .759) values obtained during the propulsive phase of BT exercises (p < 0.01). As a result, it can be suggested that upper-body strength characteristic positively affects velocity and power parameters, velocity and power characteristics are dominant and provide a significant contribution to the performance and these results will contribute to trainers and conditioners while preparing training programs in sports branches.